Measuring takaful agents’ understanding towards the objectives and concepts of takaful - Che Mohd Salleh, Marhanum; Abdullah, Nurdianawati Irwani; Razali, Siti Salwani (IIUM Press, 2013)
As the Takaful industry increasingly taking innovative steps to improvise their marketing efforts, the introduction of Wakala system (agency system) is further enhanced. Takaful agents not only oblige to sell Takaful products, but they are also responsible to educate public pertaining to the objective and importance of Takaful products. Without excellent and proper understanding, the Takaful agents would fail to fulfill their responsibility to market the Takaful products. This study thus, investigates the Takaful agents’ understanding towards the objective and concept of Takaful besides the factors that contribute to their understanding. In addition, it is done to confirm the measurement items constructed to examine the agents’ knowledge on Takaful objectives and concept. Self constructed survey questionnaire was distributed to agents of Prudential Bsn Takaful Bhd. A descriptive statistic analysis and factor analysis was utilised to measure the level of understanding among the agents and also the factors contributed to their understanding. Results indicated that the level of understanding among the Takaful agents still discontented. Furthermore, learning culture has become the most influential factor to enhance the agents’ understanding. Overall, the results of this study would reflect the Takaful industry to prepare an effective learning environment to their agents in order to strengthen their marketing efforts.